High-lead semiconductor solder wire with anti-oxidation surface and manufacturing process and application thereof
By optimizing the alloy ratio and surface treatment of high-lead semiconductor solder wire, a dense Ge oxide protective film is formed, which solves the problem of solder wire oxidation in natural environment, achieves long-term bright non-oxidation and high-temperature stability, and reduces packaging costs and usage difficulty.
Patent Information
- Application Number
- CN202511311165.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2045-09-15
AI Technical Summary
Existing high-lead semiconductor solder wires are prone to oxidation in natural environments, resulting in a dull surface that affects the soldering effect. Furthermore, they require vacuum packaging to maintain soldering performance, which increases costs and makes them more difficult to use.
By optimizing the alloy ratio and spraying a solution containing citric acid and Ge during the drawing process, Ge is enriched on the surface of the solder wire to form a dense Ge oxide. Combined with chemical surface treatment, an anti-oxidation protective film is formed to prevent oxidation.
It maintains a bright, non-oxidizing surface for up to one year under natural conditions, requires no vacuum storage, reduces packaging costs, and ensures welding quality and reliability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to a high-lead semiconductor solder wire with anti-oxidation properties on its surface, its manufacturing process, and its application, belonging to the field of welding materials technology. Background Technology
[0002] High-lead solder (typically referring to tin-lead alloys with a lead content exceeding 85%) holds an irreplaceable position in the semiconductor packaging field, primarily due to its excellent thermal fatigue reliability, high melting point (suitable for multilayer packaging structures), and coefficient of thermal expansion matching that of silicon chips. Although lead-free alternatives have emerged in the low- and medium-temperature soldering field, high-lead solder remains exempt from the EU RoHS directive and relevant Chinese regulations in high-temperature applications (such as server chips and power device packaging). This is mainly because, at high-temperature environments, no lead-free material has yet been developed that can completely replace high-lead solder.
[0003] Existing high-lead semiconductor solder wires are prone to oxidation in natural environments, resulting in a dull surface and affecting soldering performance. The main reason for the easy oxidation of traditional solder wires is the chemical reaction of their components with oxygen in the natural environment. To maintain the brightness and soldering performance of the solder wire, vacuum packaging is usually required, which increases packaging costs and inconveniences for users in terms of storage and use. Therefore, developing a high-lead semiconductor solder wire that does not require vacuum storage and remains bright and unoxidized / undulled in natural environments for at least one year has significant practical implications and market value.
[0004] High-lead semiconductor solder wires typically contain Bi (Bi). Bi's main function is to lower the solder wire's melting point, allowing for lower soldering process temperatures. Furthermore, Bi provides solid solution strengthening in Pb, improving the solder wire's strength. However, in high-lead solders, Bi dissolves within the Pb matrix. When Bi is added to a Sn-Pb system, it can alter the composition and structure of the surface oxide film. Instead of forming a uniform, continuous SnO2 protective film, a discontinuous, porous, and weakly cohesive composite oxide layer of Sn, Pb, and Bi oxides is formed. This mixed oxide layer offers inferior protection compared to a pure, dense SnO2 film. Currently, satisfactory oxidation resistance cannot be achieved in Bi-containing high-lead solders.
[0005] To address the aforementioned issues, this invention provides a high-lead semiconductor solder wire with anti-oxidation properties on its surface, along with its manufacturing process and applications. By spraying a specific solution containing citric acid and Ge onto the wire surface during the drawing process, Ge is enriched on the wire surface and reacts during subsequent drawing to form a dense Ge oxide, thus filling the porosity problem caused by Bi oxide. Summary of the Invention
[0006] The purpose of this invention is to provide a manufacturing process for a high-lead semiconductor solder wire with anti-oxidation properties on its surface. This solder wire, through optimized alloy ratio and chemical surface treatment, can achieve long-term storage without oxidation in natural environment while maintaining good soldering performance.
[0007] Meanwhile, the present invention provides a high-lead semiconductor solder wire with anti-oxidation properties on its surface.
[0008] Meanwhile, this invention provides an application of a high-lead semiconductor solder wire with anti-oxidation properties on its surface.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] A high-lead semiconductor solder wire with anti-oxidation properties on its surface comprises the following components by weight percentage:
[0011] Tin (Sn): 5%-10%;
[0012] Silver (Ag): 0.5%-1.5%;
[0013] Copper (Cu): 0.1%-0.5%;
[0014] Bismuth (Bi): 0.1%-0.3%;
[0015] Antimony (Sb): 0.1%-0.3%;
[0016] Red phosphorus (P): 0.05%-0.1%;
[0017] Germanium (Ge): 0.05%-0.1%;
[0018] Lead (Pb): Balance.
[0019] A high-lead semiconductor solder wire with anti-oxidation properties on its surface, wherein the metal elements "tin, silver, copper, bismuth, antimony and germanium" in its composition have a purity of 99.99% or higher.
[0020] Preferably, a high-lead semiconductor solder wire with anti-oxidation properties comprises the following components by weight percentage:
[0021] Tin (Sn): 5.00%;
[0022] Silver (Ag): 1.00%;
[0023] Copper (Cu): 0.40%;
[0024] Bismuth (Bi): 0.20%;
[0025] Antimony (Sb): 0.20%;
[0026] Red phosphorus (P): 0.08%;
[0027] Germanium (Ge): 0.08%;
[0028] Lead (Pb): 93.04%.
[0029] Preferably, a high-lead semiconductor solder wire with anti-oxidation properties comprises the following components by weight percentage:
[0030] Tin (Sn): 6.00%;
[0031] Silver (Ag): 1.20%;
[0032] Copper (Cu): 0.20%;
[0033] Bismuth (Bi): 0.25%;
[0034] Antimony (Sb): 0.15%;
[0035] Red phosphorus (P): 0.07%;
[0036] Germanium (Ge): 0.08%;
[0037] Lead (Pb): 92.05%.
[0038] Preferably, a high-lead semiconductor solder wire with anti-oxidation properties comprises the following components by weight percentage:
[0039] Tin (Sn): 8.00%;
[0040] Silver (Ag): 1.00%;
[0041] Copper (Cu): 0.50%;
[0042] Bismuth (Bi): 0.30%;
[0043] Antimony (Sb): 0.20%;
[0044] Red phosphorus (P): 0.05%;
[0045] Germanium (Ge): 0.06%;
[0046] Lead (Pb): 89.89%.
[0047] A manufacturing process for a high-lead semiconductor solder wire with anti-oxidation properties includes the following steps:
[0048] Step 1, Raw material preparation: Prepare each metal raw material according to the above weight percentages to ensure the purity and quality of the raw materials.
[0049] Step 2, alloy melting: Place the raw materials into a vacuum melting furnace and melt them under the protection of an inert gas at a temperature of 500-600℃. During the melting process, apply ultrasonic vibration at a frequency of 20-30kHz to ensure that all components are fully and uniformly mixed.
[0050] Step 3, casting: After applying ultrasonic vibration for 5-8 minutes, casting is carried out; the cooling rate is controlled at ≥100K / s to form solder wire blank.
[0051] Step 4, wire drawing: The billet is drawn into wires in multiple passes to gradually reduce the diameter to the required specifications. Lubricant is used during the wire drawing process to reduce friction.
[0052] During the first drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is room temperature.
[0053] During the second drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is increased to 60-80℃. Before drawing, a surface treatment solution is sprayed onto the surface of the wire. The solution composition is: Ge mass fraction 0.08-0.12%, citric acid mass fraction 1.5-2.5%, and the remainder is deionized water.
[0054] During the third drawing pass, the section shrinkage rate of the wire is controlled at 10-15%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire.
[0055] During the fourth drawing pass, the section shrinkage rate of the wire is controlled at 10-15%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire under high pressure (spray pressure 1.0-5.0MPa).
[0056] During the fifth drawing pass, the section shrinkage rate of the wire is controlled at 10-15%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire.
[0057] Continue drawing at room temperature, controlling the single-pass section shrinkage rate to 10-15%, until the wire diameter is 0.3-1mm.
[0058] Step 5, chemical surface treatment: Immerse the drawn solder wire in a chemical treatment solution containing antioxidants at a temperature of 40-60℃ for 5-10 minutes, and then dry it under inert gas protection.
[0059] The main components and formulation of the chemical treatment solution containing antioxidants are as follows: 90% deionized water, 3% ammonium phosphate, 0.05% EDTA, 0.5% octylphenol polyoxyethylene ether, 0.05% turpentine oil, and 6.4% propylene glycol methyl ether acetate.
[0060] Step Six, Finished Product Inspection: Perform visual inspection, composition analysis, and performance testing on the treated solder wire to ensure that it meets the standard requirements.
[0061] Visual inspection uses an AOI optical inspection instrument with 10x magnification to automatically check the surface of the solder wire for oil stains, spots, oxides, bumps, etc.; composition analysis is done by sampling, the main purpose of which is to control the impurity content of the alloy composition within the standard range; performance testing is also done by sampling, mainly through welding tests conducted by an automatic soldering machine to observe its fluidity and solder joint brightness, etc.
[0062] The present invention relates to the application of a high-lead semiconductor solder wire with anti-oxidation properties on its surface in semiconductor packaging.
[0063] The present invention relates to the application of a high-lead semiconductor solder wire with anti-oxidation properties on its surface in high-temperature application environments (such as server chips and power device packages).
[0064] In this invention, the addition of bismuth refines the grain size and alters the phase distribution. Bi also lowers the melting point of the welding wire, allowing for lower welding process temperatures. Furthermore, Bi exhibits a solid solution strengthening effect in Pb, which can improve the strength of the welding wire. However, in high-lead solders, Bi is dissolved in the Pb matrix. When Bi is added to the Sn-Pb system, it alters the composition and structure of the surface oxide film. Instead of forming a uniform and continuous SnO2 protective film, a discontinuous, porous, and weakly cohesive composite oxide layer of Sn, Pb, and Bi oxides is formed, resulting in poor oxidation resistance. Antimony, another important trace element, enhances the anti-oxidation performance primarily by altering the alloy surface energy to increase the surface density of the solder, significantly reducing the oxidation tendency of the alloy surface. The mechanism of action of red phosphorus is closely related to its chemical reaction in the alloy. Red phosphorus reacts with oxygen to generate stable phosphate compounds, thereby forming a protective film on the alloy surface and effectively inhibiting oxidation. In addition, the addition of trace amounts of germanium can optimize the distribution of multi-element alloy phases, refine grains, and strengthen the dense metallization film on the alloy surface.
[0065] The beneficial effects of this invention are:
[0066] (1) By optimizing the alloy ratio and chemical surface treatment, the solder wire can remain bright and non-oxidized and non-dulled within one year under natural conditions, eliminating the need for vacuum storage, thus reducing packaging costs and ease of use for users. High-temperature oxidation test results show that after being placed in an air atmosphere at 250°C for 60 hours, the solder wire obtained by this invention still maintains a bright metallic color, further proving that it can be stored at room temperature without causing severe surface oxidation.
[0067] (2) The porosity during welding will not increase due to oxidation, ensuring welding quality and reliability. Specifically, the high-lead semiconductor solder wire produced by the alloy ratio and process conditions of this invention has a more stable and dense surface structure, reducing the active sites that react with oxygen, forming a protective film with anti-oxidation effect on the surface of the solder wire, further preventing oxygen from contacting the solder wire, thereby achieving a better anti-oxidation effect.
[0068] The reason why this invention has an anti-oxidation effect on the surface of high-lead solder is mainly due to the following two mechanisms:
[0069] 1. Due to the relatively reactive chemical properties of Bi, it easily undergoes oxidation simultaneously with Sn, thus affecting the integrity of the SnO2 film and forming a loose and porous Bi2O3 film, which is a mixed film. By spraying a deionized aqueous solution containing 0.08-0.12% Ge and 1.5-2.5% citric acid on the surface of the welding wire during the second drawing pass, Ge complexes can be attached to the surface of the welding wire. Subsequently, during drawing at 60-80℃, under the influence of temperature, stress, and deformation, Ge can gradually penetrate the surface and diffuse into the interior of the welding wire, forming a dense oxide of Ge in situ during subsequent drawing passes to fill the voids in the SnO2-Bi2O3 mixed film. The gradual drawing process further densifies this oxide film layer, improving its oxidation resistance. Furthermore, spraying a deionized aqueous solution during the 3rd-5th drawing passes removes excess Ge-containing citric acid complexes from the surface of the welding wire without affecting its surface quality.
[0070] 2. According to the alloy manufacturing process of the present invention, during the preparation process, the surface of the solder wire is complexed and reacted by a chemical treatment solution containing antioxidants to generate a protective film with anti-oxidation effect on its surface, which can further increase the richness of the surface film layer and protect the solder wire material with multiple film layers. Detailed Implementation
[0071] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Example 1
[0072] A high-lead semiconductor solder wire with anti-oxidation properties on its surface comprises the following components by weight percentage:
[0073] Tin (Sn): 5.00%;
[0074] Silver (Ag): 1.00%;
[0075] Copper (Cu): 0.40%;
[0076] Bismuth (Bi): 0.20%;
[0077] Antimony (Sb): 0.20%;
[0078] Red phosphorus (P): 0.08%;
[0079] Germanium (Ge): 0.08%;
[0080] Lead (Pb): 93.04.
[0081] A manufacturing process for a high-lead semiconductor solder wire with anti-oxidation properties includes the following steps:
[0082] Step 1, Raw material preparation: Prepare each metal raw material according to the above weight percentage, ensuring the purity and quality of the raw materials. The metal elements "tin, silver, copper, bismuth, antimony and germanium" in the composition have a metal purity of 99.99% or higher.
[0083] Step 2, alloy melting: The raw materials are placed in a vacuum melting furnace and melted under the protection of an inert gas at a melting temperature of 550°C. During the melting process, ultrasonic vibration at a frequency of 25kHz is applied to ensure that the components are fully and evenly mixed.
[0084] Step 3, casting: After applying ultrasonic vibration for 6 minutes, casting is carried out; the cooling rate is controlled at 100K / s to form solder wire blank.
[0085] Step 4, wire drawing: The billet is drawn into wires in multiple passes to gradually reduce the diameter to the required specifications. Lubricant is used during the wire drawing process to reduce friction.
[0086] During the first drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is room temperature.
[0087] During the second drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is increased to 70℃. Before drawing, a surface treatment solution is sprayed onto the surface of the wire. The solution composition is: 0.10% Ge mass fraction, 2.0% citric acid mass fraction, and the remainder is deionized water.
[0088] During the third drawing pass, the section shrinkage rate of the wire is controlled at 10%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire.
[0089] During the fourth drawing pass, the section shrinkage rate of the wire is controlled at 10%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire under high pressure (spray pressure 3.0 MPa).
[0090] During the fifth drawing pass, the section shrinkage rate of the wire is controlled at 10%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire.
[0091] Continue drawing at room temperature, controlling the single-pass section shrinkage rate at 10%, until the wire diameter is 1mm.
[0092] Step 5, chemical surface treatment: Immerse the drawn solder wire in a chemical treatment solution containing antioxidants at a temperature of 50°C for 7 minutes, and then dry it under inert gas protection.
[0093] The main components and formulation of the chemical treatment solution containing antioxidants are as follows: 90% deionized water, 3% ammonium phosphate, 0.05% EDTA, 0.5% octylphenol polyoxyethylene ether, 0.05% turpentine oil, and 6.4% propylene glycol methyl ether acetate.
[0094] Step Six, Finished Product Inspection: Perform visual inspection, composition analysis, and performance testing on the treated solder wire to ensure that it meets the standard requirements.
[0095] Visual inspection uses an AOI optical inspection instrument with 10x magnification to automatically check the surface of the solder wire for oil stains, spots, oxides, bumps, etc.; composition analysis is done by sampling, the main purpose of which is to control the impurity content of the alloy composition within the standard range; performance testing is also done by sampling, mainly through welding tests conducted by an automatic soldering machine to observe its fluidity and solder joint brightness, etc.
[0096] Upon inspection, the solder wire of this embodiment remains bright and does not oxidize or darken within one year under natural conditions, eliminating the need for vacuum storage, thus reducing packaging costs and ease of use for users.
[0097] This embodiment describes the application of a high-lead semiconductor solder wire with anti-oxidation properties in semiconductor packaging.
[0098] This embodiment describes the application of a high-lead semiconductor solder wire with anti-oxidation properties on its surface in high-temperature applications (such as server chips and power device packages). Example 2
[0099] A high-lead semiconductor solder wire with anti-oxidation properties on its surface comprises the following components by weight percentage:
[0100] Tin (Sn): 6.00%;
[0101] Silver (Ag): 1.20%;
[0102] Copper (Cu): 0.20%;
[0103] Bismuth (Bi): 0.25%;
[0104] Antimony (Sb): 0.15%;
[0105] Red phosphorus (P): 0.07%;
[0106] Germanium (Ge): 0.08%;
[0107] Lead (Pb): 92.05%.
[0108] A manufacturing process for a high-lead semiconductor solder wire with anti-oxidation properties includes the following steps:
[0109] Step 1, Raw material preparation: Prepare each metal raw material according to the above weight percentage, ensuring the purity and quality of the raw materials. The metal elements "tin, silver, copper, bismuth, antimony and germanium" in the composition have a metal purity of 99.99% or higher.
[0110] Step 2, alloy melting: The raw materials are placed in a vacuum melting furnace and melted under the protection of an inert gas at a melting temperature of 500℃. During the melting process, ultrasonic vibration at a frequency of 20kHz is applied to ensure that the components are fully mixed and uniform.
[0111] Step 3, casting: After applying ultrasonic vibration for 5 minutes, casting is carried out; the cooling rate is controlled at 100K / s to form solder wire blank.
[0112] Step 4, wire drawing: The billet is drawn into wires in multiple passes to gradually reduce the diameter to the required specifications. Lubricant is used during the wire drawing process to reduce friction.
[0113] During the first drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is room temperature.
[0114] During the second drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is increased to 60℃. Before drawing, a surface treatment solution is sprayed on the surface of the wire. The solution composition is: 0.08% Ge mass fraction, 1.5% citric acid mass fraction, and the remainder is deionized water.
[0115] During the third drawing pass, the section shrinkage rate of the wire is controlled at 15%, and the drawing temperature is room temperature; deionized water is sprayed onto the surface of the wire.
[0116] During the fourth drawing pass, the section shrinkage rate of the wire was controlled at 15%, and the drawing temperature was room temperature; deionized water was sprayed onto the surface of the wire under high pressure (spray pressure 1.0 MPa).
[0117] During the fifth drawing pass, the section shrinkage rate of the wire was controlled at 15%, and the drawing temperature was room temperature; deionized water was sprayed onto the surface of the wire.
[0118] Continue drawing at room temperature, controlling the single-pass section shrinkage rate at 15%, until the wire diameter is 0.3 mm.
[0119] Step 5, chemical surface treatment: Immerse the drawn solder wire in a chemical treatment solution containing antioxidants at a temperature of 40°C for 5 minutes, and then dry it under inert gas protection.
[0120] The main components and formulation of the chemical treatment solution containing antioxidants are as follows: 90% deionized water, 3% ammonium phosphate, 0.05% EDTA, 0.5% octylphenol polyoxyethylene ether, 0.05% turpentine oil, and 6.4% propylene glycol methyl ether acetate.
[0121] Step Six, Finished Product Inspection: Perform visual inspection, composition analysis, and performance testing on the treated solder wire to ensure that it meets the standard requirements.
[0122] Visual inspection uses an AOI optical inspection instrument with 10x magnification to automatically check the surface of the solder wire for oil stains, spots, oxides, bumps, etc.; composition analysis is done by sampling, the main purpose of which is to control the impurity content of the alloy composition within the standard range; performance testing is also done by sampling, mainly through welding tests conducted by an automatic soldering machine to observe its fluidity and solder joint brightness, etc.
[0123] Upon inspection, the solder wire of this embodiment remains bright and does not oxidize or darken within one year under natural conditions, eliminating the need for vacuum storage, thus reducing packaging costs and ease of use for users.
[0124] This embodiment describes the application of a high-lead semiconductor solder wire with anti-oxidation properties in semiconductor packaging.
[0125] This embodiment describes the application of a high-lead semiconductor solder wire with anti-oxidation properties on its surface in high-temperature applications (such as server chips and power device packages). Example 3
[0126] A high-lead semiconductor solder wire with anti-oxidation properties on its surface comprises the following components by weight percentage:
[0127] Tin (Sn): 8.00%;
[0128] Silver (Ag): 1.00%;
[0129] Copper (Cu): 0.50%;
[0130] Bismuth (Bi): 0.30%;
[0131] Antimony (Sb): 0.20%;
[0132] Red phosphorus (P): 0.05%;
[0133] Germanium (Ge): 0.06%;
[0134] Lead (Pb): 89.89%.
[0135] A manufacturing process for a high-lead semiconductor solder wire with anti-oxidation properties includes the following steps:
[0136] Step 1, Raw material preparation: Prepare each metal raw material according to the above weight percentage, ensuring the purity and quality of the raw materials. The metal elements "tin, silver, copper, bismuth, antimony and germanium" in the composition have a metal purity of 99.99% or higher.
[0137] Step 2, alloy melting: The raw materials are placed in a vacuum melting furnace and melted under the protection of an inert gas at a melting temperature of 600℃. During the melting process, ultrasonic vibration at a frequency of 30kHz is applied to ensure that the components are fully mixed and uniform.
[0138] Step 3, casting: After applying ultrasonic vibration for 8 minutes, casting is carried out; the cooling rate is controlled at 100K / s to form solder wire blank.
[0139] Step 4, wire drawing: The billet is drawn into wires in multiple passes to gradually reduce the diameter to the required specifications. Lubricant is used during the wire drawing process to reduce friction.
[0140] During the first drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is room temperature.
[0141] During the second drawing pass, the section shrinkage rate of the wire is controlled at 20%, and the drawing temperature is increased to 80℃. Before drawing, a surface treatment solution is sprayed on the surface of the wire. The solution composition is: 0.12% Ge mass fraction, 2.5% citric acid mass fraction, and the remainder is deionized water.
[0142] During the third drawing pass, the section shrinkage rate of the wire was controlled at 12%, and the drawing temperature was room temperature; deionized water was sprayed onto the surface of the wire.
[0143] During the fourth drawing pass, the section shrinkage rate of the wire was controlled at 13%, and the drawing temperature was room temperature; deionized water was sprayed onto the surface of the wire under high pressure (spray pressure 1.0 MPa).
[0144] During the fifth drawing pass, the section shrinkage rate of the wire was controlled at 12%, and the drawing temperature was room temperature; deionized water was sprayed onto the surface of the wire.
[0145] Continue drawing at room temperature, controlling the single-pass section shrinkage rate at 12%, until the wire diameter is 0.5 mm.
[0146] Step 5, chemical surface treatment: Immerse the drawn solder wire in a chemical treatment solution containing antioxidants at a temperature of 60°C for 10 minutes, and then dry it under inert gas protection.
[0147] The main components and formulation of the chemical treatment solution containing antioxidants are as follows: 90% deionized water, 3% ammonium phosphate, 0.05% EDTA, 0.5% octylphenol polyoxyethylene ether, 0.05% turpentine oil, and 6.4% propylene glycol methyl ether acetate.
[0148] Step Six, Finished Product Inspection: Perform visual inspection, composition analysis, and performance testing on the treated solder wire to ensure that it meets the standard requirements.
[0149] Visual inspection uses an AOI optical inspection instrument with 10x magnification to automatically check the surface of the solder wire for oil stains, spots, oxides, bumps, etc.; composition analysis is done by sampling, the main purpose of which is to control the impurity content of the alloy composition within the standard range; performance testing is also done by sampling, mainly through welding tests conducted by an automatic soldering machine to observe its fluidity and solder joint brightness, etc.
[0150] Upon inspection, the solder wire of this embodiment remains bright and does not oxidize or darken within one year under natural conditions, eliminating the need for vacuum storage, thus reducing packaging costs and ease of use for users.
[0151] This embodiment describes the application of a high-lead semiconductor solder wire with anti-oxidation properties in semiconductor packaging.
[0152] This embodiment describes the application of a high-lead semiconductor solder wire with anti-oxidation properties on its surface in high-temperature applications (such as server chips and power device packages). Example 4
[0153] The only difference between this embodiment and Embodiment 1 is that:
[0154] A high-lead semiconductor solder wire with anti-oxidation properties on its surface comprises the following components by weight percentage:
[0155] Tin (Sn): 10.00%;
[0156] Silver (Ag): 1.5%;
[0157] Copper (Cu): 0.10%;
[0158] Bismuth (Bi): 0.10%;
[0159] Antimony (Sb): 0.10%;
[0160] Red phosphorus (P): 0.10%;
[0161] Germanium (Ge): 0.05%;
[0162] Lead (Pb): 88.05%. Example 5
[0163] The only difference between this embodiment and Embodiment 1 is that:
[0164] A high-lead semiconductor solder wire with anti-oxidation properties on its surface comprises the following components by weight percentage:
[0165] Tin (Sn): 7.00%;
[0166] Silver (Ag): 0.50%;
[0167] Copper (Cu): 0.20%;
[0168] Bismuth (Bi): 0.25%;
[0169] Antimony (Sb): 0.30%;
[0170] Red phosphorus (P): 0.07%;
[0171] Germanium (Ge): 0.10%;
[0172] Lead (Pb): 91.58%.
[0173] Comparative Example 1
[0174] The only difference between this comparative example and Example 1 is that:
[0175] During the second drawing process, deionized water is applied to the surface of the wire.
[0176] Comparative Example 2
[0177] The only difference between this comparative example and Example 1 is that:
[0178] During the fourth drawing pass, deionized water is sprayed onto the surface of the wire.
[0179] Comparative Example 3
[0180] The only difference between this comparative example and Example 1 is that:
[0181] The chemical surface treatment in step five was not performed.
[0182] Comparative Example 4
[0183] The only difference between this comparative example and Example 1 is that:
[0184] During the second drawing pass, a surface treatment solution is sprayed onto the wire surface. The solution composition is: 0.2% Ge by mass, 3.0% citric acid by mass, and the remainder is deionized water.
[0185] Comparative Example 5
[0186] The only difference between this comparative example and Example 1 is that:
[0187] During the second drawing pass, a surface treatment solution is sprayed onto the wire surface. The solution composition is: 0.05% Ge by mass, 1.0% citric acid by mass, and the remainder is deionized water.
[0188] Comparative Example 6
[0189] The only difference between this comparative example and Example 1 is that:
[0190] During the third drawing pass, deionized water is sprayed onto the wire surface under high pressure (spray pressure 3.0 MPa).
[0191] During the fourth drawing pass, deionized water is sprayed onto the surface of the wire.
[0192] Comparative Example 7
[0193] The only difference between this comparative example and Example 1 is that:
[0194] During the fourth drawing pass, deionized water is sprayed onto the surface of the wire.
[0195] During the fifth drawing pass, deionized water is sprayed onto the wire surface under high pressure (spray pressure 3.0 MPa).
[0196] The antioxidant tests and results of Examples 1-5 and Comparative Examples 1-7 are as follows:
[0197] The oxidation resistance of each welding wire was evaluated using a high-temperature oxidation test. The specific steps are as follows: First, 50g of welding wire was weighed and placed in a ceramic crucible. Then, the crucible was placed in an oven at 250℃. The color change of the welding wire was observed after a period of time (0-60h). Brightness indicated that no oxidation had occurred, dullness indicated that oxidation had occurred, and blackening of the surface indicated that more serious oxidation had occurred. In addition, the mass of the welding wire was weighed and the relative percentage of oxidation weight gain was calculated. The lower the percentage of oxidation weight gain, the better its oxidation resistance.
[0198] Specifically, the color changes of each welding wire after the high-temperature oxidation experiment are shown in Table 1 below.
[0199] Table 1
[0200]
[0201] Specifically, the percentage of oxidation weight gain of each welding wire after the high-temperature oxidation experiment is shown in Table 2 below.
[0202] Table 2
[0203]
[0204] It should be understood that, in order to simplify this disclosure and aid in understanding one or more of the various aspects of the invention, features of the invention are sometimes grouped together in a single embodiment or in its description in the foregoing description of exemplary embodiments of the invention. However, this method of disclosure should not be construed as reflecting an intention that the claimed invention requires more features than expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in fewer than all the features of the foregoingly disclosed embodiments. Therefore, the claims, following the detailed description, are hereby expressly incorporated into that detailed description, wherein each claim itself is a separate embodiment of the invention.
[0205] Although the invention has been described with reference to a limited number of embodiments, those skilled in the art will understand from the foregoing description that other embodiments are conceivable within the scope of the invention described herein. Furthermore, it should be noted that the language used in this specification has been chosen primarily for readability and instructional purposes, and not for the purpose of interpreting or limiting the subject matter of the invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the invention is illustrative and not restrictive, and the scope of the invention is defined by the appended claims.
[0206] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A high-lead semiconductor solder wire having an anti-oxidation property on the surface, characterized in that, The components include the following weight percentages: Tin: 5%-10%; Silver: 0.5%-1.5%; Copper: 0.1%-0.5%; Bismuth: 0.1%-0.3%; Antimony: 0.1%-0.3%; Red phosphorus: 0.05%-0.1%; Germanium: 0.05%-0.1%; Lead: the balance; The manufacturing process includes the following steps: Step one, raw material preparation: prepare each metal raw material according to the above weight percentages; Step two, alloy smelting: place the raw materials into a vacuum smelting furnace and smelt under inert gas protection, with a smelting temperature of 500-600°C and ultrasonic vibration applied during the smelting process with a frequency of 20-30 kHz; Step three, casting forming: after applying ultrasonic vibration for 5-8 minutes, perform casting; control the cooling speed to be ≥100 K / s to form solder wire blanks; Step four, wire drawing process: draw the blanks in multiple passes, In the first pass, control the cross-sectional reduction of the wire to be 20% and the drawing temperature to be room temperature; In the second pass, control the cross-sectional reduction of the wire to be 20% and increase the drawing temperature to 60-80°C; before drawing, spray a surface treatment solution on the surface of the wire, with the surface treatment solution having the following composition: Ge mass fraction 0.08-0.12%, citric acid mass fraction 1.5-2.5%, and the rest being deionized water; In the third pass, control the cross-sectional reduction of the wire to be 10-15% and the drawing temperature to be room temperature; spray deionized water on the surface of the wire; In the fourth pass, control the cross-sectional reduction of the wire to be 10-15% and the drawing temperature to be room temperature; spray deionized water on the surface of the wire under high pressure; In the fifth pass, control the cross-sectional reduction of the wire to be 10-15% and the drawing temperature to be room temperature; spray deionized water on the surface of the wire; Continue to draw at room temperature, with the single-pass cross-sectional reduction controlled to be 10-15%, until the diameter of the wire is 0.3-1 mm; Step five, chemical surface treatment: immerse the drawn solder wire in a chemical treatment solution containing an antioxidant, with the treatment temperature being 40-60°C and the treatment time being 5-10 minutes, and then dry under inert gas protection; Step six, finished product inspection.
2. The high-lead solder wire having an anti-oxidation surface according to claim 1, wherein the solder wire is coated with a flux containing a fluxing agent and a fluxing solvent. The components include the following weight percentages: Tin: 5.00%; Silver: 1.00%; Copper: 0.40%; Bismuth: 0.20%; Antimony: 0.20%; Red phosphorus: 0.08%; Germanium: 0.08%; Lead: 93.04%.
3. The high-lead solder wire having an anti-oxidation surface according to claim 1, wherein the solder wire is coated with a flux containing a fluxing agent and a fluxing solvent. The components include the following weight percentages: Tin: 6.00%; Silver: 1.20%; Copper: 0.20%; Bismuth: 0.25%; Antimony: 0.15%; Red phosphorus: 0.07%; Germanium: 0.08%; Lead: 92.05%.
4. The high-lead solder wire having an anti-oxidation surface according to claim 1, wherein the solder wire is coated with a flux containing a fluxing agent and a fluxing solvent. The components include the following weight percentages: Tin: 8.00%; Silver: 1.00%; Copper: 0.50%; Bismuth: 0.30%; Antimony: 0.20%; Red phosphorus: 0.05%; Germanium: 0.06%; Lead: 89.89%.
5. The high-lead semiconductor solder wire with anti-oxidation properties on its surface according to claim 1, characterized in that, In step four, a lubricant is used during the wire drawing process to reduce friction.
6. The high-lead semiconductor solder wire with anti-oxidation properties on its surface according to claim 1, characterized in that, In the fourth pass, the high-pressure spraying pressure is 1.0-5.0 MPa.
7. The high-lead solder wire having an anti-oxidation surface according to claim 1, wherein the solder wire is coated with a flux containing a fluxing agent, a fluxing solvent, and a fluxing additive. The chemical treatment solution containing antioxidant in step five has the following components and proportions: deionized water 90%, amine phosphate 3%, EDTA 0.05%, octylphenol polyoxyethylene ether 0.5%, turpentine 0.05%, and propylene glycol methyl ether acetate 6.4%.
8. The high-lead solder wire having an anti-oxidation surface according to claim 1, wherein the solder wire is coated with a flux comprising a fluxing agent, a fluxing solvent, and a fluxing additive. In step six, the finished product inspection includes appearance inspection, component analysis and performance test of the treated solder wire.
9. Application of the high-lead semiconductor solder wire with the surface having the anti-oxidation property according to any one of claims 1-8 in semiconductor packaging.
Citation Information
Patent Citations
Anti-oxidation high-temperature soft-solder solid wire and manufacturing method thereof
CN104070303A
Corrosion resistant solder alloy
JP1986273296A